Optimizing the energy storage and charge-discharge performance of borate glass-ceramics by adjusting the glass structure. Issue 4 (15th February 2022) - Du, Xinyi; Pu, Yongping; Peng, Xin; Zhang, Jinbo; Ji, Jiamin; Li, Run; Zhang, Qianwen; Chen, Min
Abstract: In this work, the niobate-based borate glass-ceramic system K2 O–Na2 O–Nb2 O5 –B2 O3 was proposed for the first time, in which the presence of alkali metal oxides not only tends to form ferroelectric crystalline phase to obtain high permittivity, but also optimizes the borate glass network structure to enhance the breakdown strength. The change of borate glass network structure and the influence on conductivity and carriers migrate is systematically discussed. The results show that the high breakdown performance is attributed to the transformation from [B∅2 O − ] triangle to [B∅4 ] - tetrahedron realizes the high extent of glass network polymerization, which effectively impedes carriers migration and reduces the conductivity. The high permittivity and low dielectric loss are obtained in the range of room temperature to 200 °C. Compared to other niobate-based glass-ceramics, the potassium sodium niobate borate glass-ceramic simultaneously achieve high discharge energy density, high power density and rapid discharge rate (∼14 ns).